Perancangan Pengalaman Pengguna Aplikasi Pembayaran Retribusi Menara berbasis Mobile menggunakan Metode Design Thinking (Studi Kasus: Dinas KOMINFO Kabupaten Bondowoso) - Tiffani Nisa Zulaikah; Herman Tolle; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The development of telecommunications towers every year experiences rapid development. One of them is the construction of towers in the Bondowoso area, according to data from the KOMINFO Service of Bondowoso Regency, there are 148 towers with 11 providers who have construction permits. This can increase the source of Regional Original Income (PAD) through tower levies. The local government wants the producing agency to be able to accelerate the digitization of transactions within the Bondowoso Regency Government as a form of expanding the implementation of the Regional Government Transaction Electronification (ETP) in 2021. So the purpose of this research is to provide a solution design in the form of designing a mobile-based tower levy payment application user experience so that can improve the tower levy management system. The application of the method in this study uses the Design Thinking method because it can solve quite complex problems and focuses on understanding user problems so that it can produce various solutive innovations. At the usability testing stage, 3 evaluators used the Heuristic Evaluation method. It was found that 17 usability problems were agreed upon with the most results being on the principle of heuristic number H2 (Match between system and the real world) and H6 (Recognition rather than recall), namely 5 problems with a percentage of 19.23%. While the average value of the highest severity rating is found on the principle of heuristic number H3 (User control and freedom) with a value of 3 and is included in the major category.